Evaluation of Changes in Macular Thickness following Nepafenac Ophthalmic Drops in Chronic Diabetes - jahanzaib, Muhammad; Humayun, Fakhar; Naseer, Saad; Tariq, Usman; Khan, Fawad Ahmad; butt, Waqas Rahim (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the efficacy of Nepafenac ophthalmic drops in reducing macular inflammation and thickness in chronic diabetic retinopathy using optical coherence tomography (OCT). Study Design: Quasi-experimental study. Place and Duration of Study: Department of Ophthalmology, Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Jan to Dec 2023. Methodology: Before initiating treatment, visual acuity was assessed using a standard Snellen chart and documented in the patient records. Baseline foveal thickness was measured in all participants using optical coherence tomography (OCT). All patients then started on 0.1% Nepafenac ophthalmic drops, administered as one drop in each eye twice daily for six months. The primary outcome measures were the change in visual acuity and the change in mean foveal thickness, both evaluated after six months using OCT. Results: Change in visual acuity (converted from Snellen values to LogMAR) was 0.79±0.21 log units before starting medical treatment, and it was 0.62±0.16 after six months of medical therapy (p<0.001). Change in foveal thickness as assessed by OCT (optic coherence tomography) was 472.14±76.02 microns before the start of medical therapy, and it was 253.69±47.26 microns after six months of treatment (p<0.001). Conclusion: The study concludes that Nepafenac ophthalmic drops effectively improve macular edema, reduce foveal thickness, and enhance visual acuity in patients with diabetic retinopathy who present with a pre-treatment visual acuity of less than 6/12 on the Snellen Chart.